Heart rate-based training intensity and its impact on injury incidence among elite-level professional soccer players - Owen, A. L.; Forsyth, J. J.; Wong, D. P.; Dellal, A.; Connelly, S. P.; Chamari, K. (The Journal of Strength and Conditioning Research, 2015)
Elite-level professional soccer players are suggested to have increased physical, technical, tactical, and psychological capabilities when compared with their subelite counterparts. Ensuring these players remain at the elite level generally involves training many different bodily systems to a high intensity or level within a short duration. This study aimed to examine whether an increase in training volume at high-intensity levels was related to injury incidence, or increased the odds of sustaining an injury. Training intensity was monitored through time spent in high-intensity (T-HI) and very high-intensity (T-VHI) zones of 85-<90% and =90% of maximal heart rate (HRmax), and all injuries were recorded over 2 consecutive seasons. Twenty-three, elite professional male soccer players (mean ± SD age, 25.6 ± 4.6 years; stature, 181.8 ± 6.8 cm; and body mass, 79.3 ± 8.1 kg) were studied throughout the 2-years span of the investigation. The results showed a mean total injury incidence of 18.8 (95% confidence interval [CI], 14.7-22.9) injuries per 1,000 hours of exposure. Significant correlations were found between training volume at T-HI and injury incidence (r = 0.57, p = 0.005). Further analysis revealed how players achieving more time in the T-VHI zone during training increased the odds of sustaining a match injury (odds ratio = 1.87; 95% CI, 1.12-3.12, p = 0.02) but did not increase the odds of sustaining a training injury. Reducing the number of competitive match injuries among elite-level professional players may be possible if greater focus is placed on the training intensity and volume over a period of time ensuring the potential reduction of fatigue or overuse injuries. In addition, it is important to understand the optimal training load at which adaptation occurs without raising the risk of injury.